IMPACTS OF BIOLOGICAL SOIL CRUST DISTURBANCE AND COMPOSITION ON C AND N LOSS FROM WATER EROSION - Barger N.N.; Herrick J.E.; Van zee Ju.; Belnap Ja. (My University, 2006)
In this study, we conducted rainfall simulation experiments in a cool desert ecosystem to examine the role of biological soil crust disturbance and composition on dissolved and sediment C and N losses. We compared runoff and sediment C and N losses from intact late-successional dark cyanolichen crusts (intact) to both trampled dark crusts (trampled) and dark crusts where the top 1 cm of the soil surface was removed (scraped). In a second experiment, we compared C and N losses in runoff and sediments in early-successional light cyanobacterial crusts (light) to that of intact late-successional dark cyanolichen crusts (dark). A relatively high rainfall intensity of approximately 38 mm per 10-min period was used to ensure that at least some runoff was generated from all plots. Losses of dissolved organic carbon (DOC), dissolved organic nitrogen (DON), and ammonium (NH 4 + ) were significantly higher from trampled plots as compared to scraped and intact plots. Sediment C and N losses, which made up more than 98% of total nutrient losses in all treatments, were more than 4-fold higher from trampled plots relative to intact plots (sediment C g/m2, intact = 0.74, trampled = 3.47; sediment N g/m2, intact = 0.06, trampled = 0.28). In light crusts, DOC loss was higher relative to dark crusts, but no differences were observed in dissolved N. Higher sediment loss in light crusts relative to dark crusts resulted in 5-fold higher loss of sediment-bound C and N. Total C flux (sediment + dissolved) was on the order of 0.9 and 7.9 g/m2 for dark and light crusts, respectively. Sediment N concentration in the first minutes after runoff from light crusts was 3-fold higher than the percent N of the top 1 cm of soil, suggesting that even short-term runoff events may have a high potential for N loss due to the movement of sediments highly enriched in N. Total N loss from dark crusts was an order of magnitude lower than light crusts (dark = 0.06 g N/m2, light = 0.63 g/m2). Overall, our results from the small plot scale (0.5 m2) suggest that C and N losses are much lower from intact late-successional cyanolichen crusts as compared to recently disturbed or early-successional light cyanobacterial crusts.
Keywords: BIOLOGICAL SOIL CRUST; CARBON; CANYONLANDS NATIONAL PARK; COLORADO PLATEAU; DISTURBANCE; EROSION; NITROGEN; RAINFALL SIMULATION; RUNOFF